Mechanism and cis/trans Selectivity of Vinylogous Nazarov-type [6π] Photocyclizations - Pusch, Stefan; Lefrancois, Daniel; Dreuw, Andreas (The journal of organic chemistry, 2018)
Vinylogous Nazarov-type cyclizations yield seven-membered rings from butadienyl vinyl ketones via a photochemical [6π] photocyclization followed by subsequent isomerization steps. The mechanism of this recently developed method was investigated using unrestricted DFT, SF-TDDFT, and CASSCF/NEVPT2 calculations, suggesting three different pathways that lead either to pure trans, pure cis, or mixed cis/trans configured products. Singlet biradicals or zwitterions occur as intermediates. The computational results are supported by deuterium-labeling experiments.
Published: December 22, 2017
Gesehen am 15.05.2020